Anticataract activity of ethanolic extract from Hippobroma longiflora (L.) G.Don leaves: Ex vivo investigation - Eva Imelda; Khairan Khairan; Rodiah R. Lubis; Pati Kemala; Utari Zulfiani; Suci Rahayu; Ghazi M. Idroes; Sarra M. Adev; Nur B. Maulydia; Rinaldi Idroes (Journal of Pharmacy & Pharmacognosy Research, 2023)
Context: In Aceh, Hippobroma longiflora, known as kitolodby the locals, is believed to possess medicinal benefits such as anticataract.